2014
DOI: 10.2310/jim.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prostaglandin I2 Analogs on Macrophage Inflammatory Protein 1α in Human Monocytes via I Prostanoid Receptor and Cyclic Adenosine Monophosphate

Abstract: Prostaglandin I2 analogs suppressed LPS-induced MIP-1α production in human monocytes via the IP receptor and cAMP pathway. The PGI2 analog may be potential in the treatment for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…PGs E 2 and I 2 , and cysteinyl leukotrienes). In turn, these eicosanoids can modulate chemokine production in monocytes and macrophages (Hashimoto et al ., ; Ichiyama et al ., ; Kuo et al ., ; Buenestado et al ., ; Tsai et al ., ). Furthermore, 15‐HETE can be also produced via COX‐dependent pathways (Levy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…PGs E 2 and I 2 , and cysteinyl leukotrienes). In turn, these eicosanoids can modulate chemokine production in monocytes and macrophages (Hashimoto et al ., ; Ichiyama et al ., ; Kuo et al ., ; Buenestado et al ., ; Tsai et al ., ). Furthermore, 15‐HETE can be also produced via COX‐dependent pathways (Levy et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, PGI 2 has inhibitory effects on the activation of endothelial cells and on the proliferation and migration of smooth muscle cells (41)(42)(43). PGI 2 acts on leukocytes stimulating the production of anti-inflammatory cytokines and inhibiting the release of IL-1, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ. PGI 2 also regulates macrophage functions, promoting their anti-inflammatory profile (44,45). Effects on the inhibition of platelet aggregation have also been described (20,43).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PPARα can regulate the expression of other chemokines, such as macrophage inflammatory protein-1α (MIP-1α). Tsai et al have reported that prostaglandin I2 analogs inhibit LPS-induced MIP-1α production in THP-1 cells and human primary monocytes by upregulation of PPARα [100]. Overall, PPARα-mediated downregulation of MCP-1 and MIP-1α also plays critical roles in the limitation of vascular inflammation during atherogenesis.…”
Section: Pparα Limits Vascular Inflammationmentioning
confidence: 91%